How to survive in the alcohol industry or advertising technologies of alcohol brands - Sattarov T. A., Gataullina L. V., Mefodeva M. A. (Education and science in the modern context, 2018)
this article considers the technologies of the alcohol brand formation. The advertising campaigns of the leading brands are analyzed. The peculiarities of using advertising methods, concepts and technologies are revealed. Based on the study, several specific advertising technologies are published, which are most effective in practical application.
Keywords: алкоголь; реклама; бренд; internet; leader; social media; image; social networks; рекламные технологии; рекламные кампании; political PR; politician